Evolusi Jihad dalam Al-Quran: Satu Tinjauan Sejarah - Abdullah, Mustaffa (Jurnal Usuluddin, 1997)
The aim of this article is to expose the evolution of jihad in accordance to the Qur'an. This evolution has brought many advantages to Islam and it's followers, who try to realise their responsibilities in true meaningful words.